1998
DOI: 10.1021/la962060h
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Crystals and Colloids in Water−Amiodarone Systems

Abstract: Amiodarone, a molecule used in treatment of heart arrhythmias, presents several metastable states. Transparent sols (50 mg/mL) and gels (100 mg/mL) are obtained by heating amiodarone crystals in water to 70 °C and cooling to 20 °C. These preparations diluted in water remained transparent above 1.5 mg/mL, but further dilutions resulted in a milky cloud, which was studied by light scattering and photon correlation spectroscopy. A swollen smectic phase appeared at 200 mg/mL and another isotropic gel at 500 mg/mL.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 14 publications
0
12
1
Order By: Relevance
“…A lot of pharmacologically active molecules are amphiphilic and form liquid crystalline phases in presence of water, amiodarone for instance [15] and this is an essential point in the perspective of nanoparticle preparation [16]. Many waterelipid systems are used to prepare diverse creams.…”
Section: Discussion: Liquid Crystals In Cells Tissues and Medicamentsmentioning
confidence: 99%
“…A lot of pharmacologically active molecules are amphiphilic and form liquid crystalline phases in presence of water, amiodarone for instance [15] and this is an essential point in the perspective of nanoparticle preparation [16]. Many waterelipid systems are used to prepare diverse creams.…”
Section: Discussion: Liquid Crystals In Cells Tissues and Medicamentsmentioning
confidence: 99%
“…NMR studies indicated a reversible disruption of aggregates at 60°C [9]. This clear phase defined as a pseudo-solution [10] ceased to be transparent and showed a milky opalescence at room temperature, when diluted at concentrations close to the CMC. This behavior is not typical of surfactants close to the CMC and is an indication that some of the data reported in literature may be misinterpreted.…”
Section: Introductionmentioning
confidence: 97%
“…For example, the intrinsic solubility of amiodarone (3,9,11) is onerous to measure accurately, in part because of the tendency of the drug to form multiple metastable gels, which can persist for as long as a month (18). Aggregation (14Y Y Y16) and micelle formation (17,18), common with lowsolubility molecules, can hamper the interpretation of the measurements.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the intrinsic solubility of amiodarone (3,9,11) is onerous to measure accurately, in part because of the tendency of the drug to form multiple metastable gels, which can persist for as long as a month (18). Aggregation (14Y Y Y16) and micelle formation (17,18), common with lowsolubility molecules, can hamper the interpretation of the measurements. Roseman and Yalkowsky (19) described the solubilityY Y YpH behavior of prostaglandin F2a and noted that anionic aggregates appeared to form (Case 2a in BTHEORETICAL SECTION^), since the ascending portion of the solubilityY Y YpH curve was shifted to lower pH values than predicted by the HendersonY Y YHasselbalch equation.…”
Section: Introductionmentioning
confidence: 99%